Plastics to fuel : effect of plastic to oil palm ash catalyst weight ratio and plastic types - Mohd Ali, Mohd.Kucheb (2017)
Depleting of fossil fuel leads to exploration of alternative fuel production including converting waste to fuel. Converting of plastic to fuel via pyrolysis can be done but low yield and fuel quality are the major obstacles to commercialize this technology. The objective of this investigation is to study the effect of plastic to catalyst weight ratio and plastic type in catalytic pyrolysis of plastic to fuel. Four type of plastics; namely Low Density Polyethylene (LDPE), High Density Polyethylene (HDPE), Polypropylene (PP) and Polystyrene (PS), were used. Thermal decomposition study of the plastics was done by using Thermogravimetric Analyser. The plastic to catalyst weight ratio was varied from 5:1 to 10:1. An oil palm biomass ash was used as a catalyst. The catalyst was cleaned and calcined at 750C for four hours. The catalyst was characterized by using Scanning Electron Microscope (SEM), Brunauer, Emmett and Teller (BET) and Thermogravimetry Analyser (TGA). Nitrogen gas was used to provide oxygen free condition during the investigation. The catalyst was tested in a batch one litre borosilicate reactor and heated up to 450C for 30 minutes. The liquid product was collected in a condenser, while the uncondensed gases was collected in the gas bag. The physical appearance, calorific value, moisture, density, cetane and octane number of the liquid product was determined. The composition of the liquid fuel was verified by using Mass Spectrometric Gas Chromatography (GC-MS). The gas composition in the gas product was analysed via Thermal Conductivity Detector Gas chromatography (GC-TCD). The best yield of liquid product was obtained when Polystyrene was used and yielded 6.25% of gas, 84.36% of liquid fuel and 9.2% of solid product. Liquid fuel quality with averagely low moisture (about 2.2%), high calorific value (2408 cal/g), and clear liquid with turbidity of 9.23 NTU was achieved. A gas product that rich in methane (0.25 mol%) was obtained from PP plastic. In conclusion, a low cost alternative fuel production via catalytic plastic waste pyrolysis was achieved.